Design Process and Remote Work: The importance of Problem Immersion to understand the right to disconnect - Freire Florentino, Viviane; Florêncio de Sousa, Ana Luisa; dos Santos de Assis, Maria Consuelo; dos Santos, André Luiz; Silveira Ferreira, Suzana Maria; Nascimento Santiago Caminha, Camille (Convergences - Journal of Research and Arts Education, 2022)
After the start of COVID19 pandemic in 2020, remote work has become an imposing working mode for some workers in organizations whose home office culture had not yet been adopted. This scenario led to the development of this article, which aims to present the importance of immersion in the problem within the design process, using as an object the problem of the super connected employee and his right to disconnect. For this, we did an exploratory case study, using qualitative design techniques to explore problems regarding Remote Working. The results allowed us to observe how deep dive in real data helped us to understand the problem in depth, and how the understanding, definition and validation of the problem helped in insights generation.